The link between economic growth and emigration from developing countries: Does migrants' skill composition matter? - Mauro Lanati; Rainer Thiele (Kyklos, 2023)
Tackling the root causes of migration from developing countries through development cooperation has been suggested as an essential part of the policy mix in OECD migrant destinations. This is even though the evidence on whether economic development leads to more or less people emigrating is so far inconclusive. We investigate the relationship between income per capita and emigration to OECD countries separately for three different skill groups—low-skilled, medium-skilled and high-skilled emigrants—being the first to employ panel regression approaches that account for cross-country heterogeneity and cover a policy-relevant time frame of about 50.167emyears. Our findings reveal a universal negative association between income per capita and emigration for all three skill groups and for different income thresholds. This implies that policy makers should not be too concerned about potential trade-offs between (successful) development cooperation and immigration management, at least in the short to medium run that our analysis covers. At the same time, the scope for using development cooperation as a migration policy instrument can be considered to be limited given the modest size of the estimated income effect: Taking our point estimates at face value, a 10% rise in GDP per capita would on average lead to about 3600 fewer immigrants per destination.
Keywords: 330; Economic Development; Migrants' Skill Composition; Migration